Evaluating LRRK2 Genetic Variants with Unclear Pathogenicity - Refai, Fathima Shaffra (Biomed Res Int, 2015)
Mutations in the leucine-rich repeat kinase 2 (LRRK2) have been known to be a major genetic component affecting Parkinson's disease (PD). However, the pathogenicity of many of the LRRK2 variants is unclear because they have been detected in single patients or also in patients and controls. Here, we selected 5 exonic variants (L1165P, T1410M, M1646T, L2063X, and Y2189C) from each of the protein domain of LRRK2 and analysed their possible association with pathogenicity using in vitro functional assays. Point mutations representing each of these variants were incorporated into the LRRK2 gene, and functional aspects such as the percentage of cell survival upon application of stress and kinase activity were measured. Our results showed that all 5 variants had a significantly negative effect on the survival of cells, in both presence and absence of stress, as compared to the wild-type. In addition, there was also a slight increase in kinase activity in most of the variants in comparison to the wild-type. A negative correlation between cell survival and kinase activity was observed. These data suggest that most of the variants despite being located in different domains of LRRK2 appear to exert a potential pathogenic effect possibly through an increased kinase activity, supporting a gain of function mechanism.